Cortes sonoros: músicas, apropiaciones, contextos (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2021)
Sampling is very popular amongst commercial music, although it is also present in electroacoustic or acousmatic music as well as soundscapes, radio-art, sound-art and other non-musical media from radio transmissions and television like speeches, advertisements, and others. Artistic expressions like collage, meta collage, appropriation, intervention, plunderphonic, remix, parody, allusion and paraphrasing have become part of the landscape of contemporary artistic creation; they usually have ambiguous boundaries but without being a problem for the musicians/composers. It’s safe to say, without a doubt, that sampling, or sampling culture, is one of the most innovative and active movements of the last decades. But what are its origins? Under which circumstances did we began to consider using previously recorded and distinguishable pieces? Why does a creator/composer chooses to use a pre-recorded musical fragment, and what does it mean for the listener?
Keywords: sound; referentialiy; quote; appropiation